2018
DOI: 10.1186/s12870-018-1469-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PvCO1, a bamboo CONSTANS-LIKE gene, delays flowering by reducing expression of the FT gene in transgenic Arabidopsis

Abstract: BackgroundIn Arabidopsis, a long day flowering plant, CONSTANS (CO) acts as a transcriptional activator of flowering under long day (LD) condition. In rice, a short day flowering plant, Hd1, the ortholog of CO, plays dual functions in respond to day-length, activates flowering in short days and represses flowering in long days. In addition, alleles of Hd1 account for ~ 44% of the variation in flowering time observed in cultivated rice and sorghum. How does it work in bamboo? The function of CO in bamboo is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…In recent years, COL transcription factors have been identified in many plants, such as Arabidopsis thaliana (Zhang et al, 2014), Brassica juncea (Muntha et al, 2019), Phyllostachys violascens (Xiao et al, 2018), and Oryza sativa (Sheng et al, 2016). Most COL transcription factors have been reported to be involved in flowering regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, COL transcription factors have been identified in many plants, such as Arabidopsis thaliana (Zhang et al, 2014), Brassica juncea (Muntha et al, 2019), Phyllostachys violascens (Xiao et al, 2018), and Oryza sativa (Sheng et al, 2016). Most COL transcription factors have been reported to be involved in flowering regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that studies for bamboo protein subcellular localization and protein-protein interaction have been reported only in heterologous expression. Usually, bamboo proteins are fluorescence tagged and expressed in rice protoplasts, onion epidermal cells, or tobacco leaves (Ge et al, 2017;Liu et al, 2018;Xiao et al, 2018). However, different expression patterns may arise from heterologous systems (Marion et al, 2008), and we have also found that several fluorescence-tagged proteins were functional in the Arabidopsis transient expression system but were not expressed or did not show similar subcellular distribution in moso bamboo protoplasts.…”
Section: Organelle Markers In the Moso Bamboo Endomembrane Systemmentioning
confidence: 83%
“…Over the past decade, a set of organelle markers containing multicolored fluorescent tags have been developed in Arabidopsis and rice and used for co-localization studies with transient expression method (Nelson et al, 2007). Up to now, the subcellular localization of bamboo proteins has been mostly studied in heterologous plants such as Arabidopsis and rice leaf protoplasts (Ge et al, 2017;Zhang et al, 2018), onion epidermal cells (Xiao et al, 2018), or tobacco leaves (Liu et al, 2018). However, ectopic expression of proteins in different plant species may result in mis-localization because of the non-conservation of signal sequences or posttranscriptional modifications in the heterologous expression system (Marion et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…CRA1 was expressed during flowering, petal differentiation, and expansion (Li et al, 2008; Sekhon et al, 2012), and in collective leaf structure, flower, petal, pollen, and sepal (Shapiguzov et al, 2016; Robinson et al, 2018). HIPP25 was expressed in LP.04 at the four-leaves-visible stage and in LP.06 at the six-leaves-visible, flowering, petal differentiation, and petal expansion stages (Jiang et al, 2012; Ogawa et al, 2015; Xiao et al, 2018) and in the carpel, leaf apex, petal, plant embryo, pollen, root, sepal, stamen, stem, and leaf vasculature (Chauvin et al, 2013; Shapiguzov et al, 2016; Luo et al, 2018). These two cov QTLs are major contributors to leaf growth and biomass accumulation in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%